Kebijakan Efisiensi Dalam Pengelolaan Anggaran Negara Di Indonesia Tahun 2025 Ditinjau Dari Perspektif Siyasah Maliyyah - Mallongi, Andi Agung; Athoriq. R, Muhammad Aqsho Che; Qolby, Annisa Nur Azifah; Agustin, Aswidia; Saputra, Anjas (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The management of the state budget plays a strategic role in realizing public welfare and reflects good governance practices. As an integral part of fiscal policy, the state budget is required to be managed fairly, transparently, and efficiently to meet public needs and support national development. From an Islamic perspective, the concept of state financial management is known as siyasah maliyyah, which refers to government policies in managing public finances to achieve the common good (maslahah). This study aims to analyze efficiency policies in state budget management based on the perspective of siyasah maliyyah, as well as to identify strategic steps that can enhance the effectiveness of public financial management. This research uses a qualitative approach with a library research method that emphasizes content analysis of literature related to the research topic. The data sources consist of primary data in the form of Presidential Instruction (Inpres) Number 1 of 2025 concerning Expenditure Efficiency in the Implementation of the State Budget (APBN) and Regional Budget (APBD) for the Fiscal Year 2025, classical Islamic literature such as fiqh books by prominent scholars, and secondary data in the form of scientific journals, books, policy reports, and official documents relevant to budget management. Data collection techniques were carried out through document review and literature study, while data analysis employed descriptive qualitative analysis to evaluate and interpret data content based on the principles of siyasah maliyyah. The results of the study show that the application of the principles of justice, transparency, and accountability in siyasah maliyyah is a crucial foundation for effective and efficient state budget management. Budget policies should focus on improving equitable budget distribution that is responsive to public needs, strengthening fiscal autonomy, and utilizing technology to enhance transparency and accountability.